An Undercooled Scree Slope Detected by Geophysical Investigations in Sporadic Permafrost below 1000 M ASL, Central Austria. (July 2014) - Stiegler, Christian; Rode, Matthias; Sass, Oliver; Otto, Jan‐Christoph
ABSTRACT Multi‐method geophysical investigations, accompanied by microclimatic measurements and vegetation mapping, were performed at an undercooled scree slope near Schladming (Austria) in the eastern Alps in order to detect, map and monitor mountain permafrost. The study site, at an elevation of 990 m asl, is one of the lowest‐lying examples of a cold, undercooled scree slope in the Alps. Geophysical measurements with electrical resistivity tomography, ground‐penetrating radar and seismic refraction indicate the presence of several isolated areas of frozen ground over a full year, far below the regional lower limit of mountain permafrost. Frozen sediments identified at shallow depths (beneath 1–3 m) were 5–20 m thick and ice‐rich. Near‐surface temperatures at the foot of the scree slope were strongly influenced by pronounced cooling. Vegetation mapping showed a dominance of cryophilic plant species. The results suggest that the scree slope is strongly influenced by the interplay of vegetation cover, ground thermal regime and the distribution of frozen sediments. Copyright © 2014 John Wiley & Sons, Ltd.